Նախադպրոցական տարիքի երեխայի տագնապայնության դրսեվորման հոգեբանական պատճառներն և հաղթահարման ուղիները - Ստեփանյան, Ն. Ե. (Մանկավարժ հրատ․)
Статья посвящена проблеме тревожности. Рассматриваются психологические проявления и причины высокой тревожности у детей дошкольного возраста и пути ее преодоления. Часто семейные конфликты, холодные взаимоотношения между родителями и детьми являются причиной для появления высокой тревожности у детей. The article is dedicated to the problem of anxiety. In this article considered the psychological performance and the causes of preschool children’s high anxiety, as well as the ways to overcome the problem are discussed In this article. Frequently the family conflicts, cold relationship between parents and children are the causes for the high anxiety of children.
Keywords: Հոգեբանություն